Networks, Digital Libraries and Knowledge Management: Trends & Developments - Ghose, Maitrayee; Jambhekar, Ashok (DESIDOC Journal of Library & Information Technology, 2003)
The work culture in libraries has changed due to the growth of computer networks and the World Wide Web. The growth of interest in knowledge management (KM) has essentially been contemporary with that of intranets/extranets. It is no longer sufficient for libraries to depend solely on having sufficient access to internal and external information resources but to efficiently exploit what the system actually knows—not only what it owns. The successful implementation of KM is that people will share what they know and reuse the know how of others; from this perspective, paper examines the changing role and core competencies required for information professionals specially as a chief knowledge officer (CKO). It also focuses on the vision, strategy and appropriate mind set required for successful implementation without which knowledge management can become an empty slogan. http://dx.doi.org/10.14429/dbit.23.5.3607